Study of Infiltration Soil Rate in Some Lands Using at Desa Tongkoh Kecamatan Dolat Rayat Kabupaten Karo - Ahmad Eka Putra; Sumono Sumono; Nazif Ichwan; Edi Susanto (Jurnal Rekayasa Pangan dan Pertanian, 2013)
The aim of this research was to know the infiltration rate in some land uses at Desa Tongkoh Kecamatan Dolat Rayat Kabupaten Karo using Philips equation model. The land uses i.etomato field, avocado field, and pine forest were observed. Parametersobserved were moisture content, soil texture, organic matter, bulk density, particle density, porosity, cumulative infiltration. Double ring infiltrometer that pressed into the soil were used in this research. The decreased of water level was observed with interval of 0, 5, 10, 20, 30, 45, 60, 120, 180, 240 minutes. The results for every land uses showed that the highest infiltration was found in tomato field, and pine forest, the lowest was found in avocado field. Factorsaffected the infiltration rate were soil texture, porosity and organic matter. Key word: Infiltration Rate, Tomato Field, Avocado Field, Pine Forest, Tongkoh Village